Learning styles of urban and rural black South African children - Meyerowitz, Gabrielle (My University, 2014)
The learning styles of 30 urban and 30 rural black children were rated by their teachers, using the Learning Style Identification Inventory. The results obtained frtiin the teachers of the rural sample were found to be inaccurate. It was therefore not possible to make comparisons with previous findings. The results of the urban sample suggest that, on the Abstract-Concrete dimension their learning styles tended towards the Concrete end of the dimension, and on the Verbal-imaginal dimension, their ratings tended towards the Imaginal end of the dimension. An analysis of variance and Bonferroni / test indicated that these children were rated significantly more Imaginal than Verbal and significantly more Concrete than Abstract These findings are in contrast with previous research in other countries and tentatively suggest that urban children in South Africa are functioning in a manner more consistent with findings regarding learning styles of rural children in other countries. This has implications for teachers and the teaching styles of teachers in urban schools.
Keywords: Learning ability; Cognitive psychology; Learning, Psychology of; Educational psychology; School children--South Africa; Blacks--Education--South Africa